Simulating an ultra-broadband concept for Exawatt-class lasers - Zhaoyang Li (Nature Portfolio, 2021)
Abstract The rapid development of the optical-cycle-level ultra-fast laser technologies may break through the bottleneck of the traditional ultra-intense laser [i.e., Petawatt (PW, 1015 W) laser currently] and enable the generation of even higher peak-power/intensity lasers. Herein, we simulate an ultra-broadband concept for the realization of an Exawatt-class (EW, 1018 W) high peak-power laser, where the wide-angle non-collinear optical parametric chirped-pulse amplification (WNOPCPA) is combined with the thin-plate post-compression. A frequency-chirped carrier-envelope-phase stable super-continuum laser is amplified to high-energy in WNOPCPA by pumping with two pump-beamlets and injected into the thin-plate post-compression to generate a sub-optical-cycle high-energy laser pulse. The numerical simulation shows this hybrid concept significantly enhances the gain bandwidth in the high-energy amplifier and the spectral broadening in the post-compression. By using this concept, a study of a prototype design of a 0.5 EW system is presented, and several key challenges are also examined.